Exodus and Deuteronomy - Brenner-Idan, Athalya; Yee, Gale A., 1949- (Texts @ contexts., 2012)
"The Texts @ Contexts series gathers scholarly voices from diverse contexts and social locations to bring new or unfamiliar facets of biblical texts to light. Exodus and Deuteronomy focuses attention on two books of the Torah that share themes of journey and of diverse experiences in or upon the land; the echoes of the exodus across time, space, and culture; of different understandings of (male and female) leadership; and of the promise, and problem, posed by various aspects of biblical law. These essays de-center the often homogeneous first-world orientation of much biblical scholarship and open up new possibilities for discovery"--Publisher description